Difficulties in Making the Ethically Correct Choice in the Management of a Case of Proven Dangerousness of a Shelter Dog - Benedetti, R. (Journal of applied animal ethics research, 2020)
The management of shelter dogs whose dangerousness to people has been verified is an aspect of considerable importance as it assesses animal welfare, public health, and the management of human and economic resources. In this paper, we briefly discuss the case of a large sized male dog that had bitten people several times and was declared to be at high risk of causing danger. Despite a behavioral rehabilitation program, the initial evidence of dangerousness remained unchanged, thus, there was no possibility of putting the dog up for adoption. This clinical case is an example of how conflicting it is for a behaviorist to choose ethically when considering euthanasia and animal welfare.